Work Discipline on the Performance of MSMEs Adelia Capcin - Fikri Ikhlasun Amal; Irvan Lismana; Dwi Epty Hidayaty; Santi Pertiwi Hari Sandi (PT FORMOSA CENDEKIA GLOBAL, 2023)
Quality human resources are one of the factors that will determine the success of any organization. Work discipline is very important and must be possessed by leaders and employees. Leadership means involving others, namely subordinates or employees who are led. Adelia Capcin is an MSME business venture engaged in culinary, just like other MSME businesses. The purpose of this observation is to know and analyze the effect of work discipline on employee performance, to know and analyze the influence of motivation on employee performance and to know and analyze the effect of work discipline and motivation on employee performance on Adelia Capcin. This observation uses HR theory related to work discipline, employee motivation and performance. This observation uses a descriptive approach method. The results of these observations reveal the motivation and work discipline of Adelia Capcin's MSME business.